Association between perceived insufficient sleep, frequent mental distress, obesity and chronic diseases among US adults, 2009 behavioral risk factor surveillance system - Liu Yong; Croft Janet B; Wheaton Anne G; Perry Geraldine S; Chapman Daniel P; Strine Tara W; McKnight-Eily Lela R; Presley-Cantrell Letitia (BMC, 2013)
Abstract Background Although evidence suggests that poor sleep is associated with chronic disease, little research has been conducted to assess the relationships between insufficient sleep, frequent mental distress (FMD ≥14 days during the past 30 days), obesity, and chronic disease including diabetes mellitus, coronary heart disease, stroke, high blood pressure, asthma, and arthritis. Methods Data from 375,653 US adults aged ≥ 18 years in the 2009 Behavioral Risk Factor Surveillance System were used to assess the relationships between insufficient sleep and chronic disease. The relationships were further examined using a multivariate logistic regression model after controlling for age, sex, race/ethnicity, education, and potential mediators (FMD and obesity). Results The overall prevalence of insufficient sleep during the past 30 days was 10.4% for all 30 days, 17.0% for 14-29 days, 42.0% for 1-13 days, and 30.6% for zero day. The positive relationships between insufficient sleep and each of the six chronic disease were significant (p < 0.0001) after adjustment for covariates and were modestly attenuated but not fully explained by FMD. The relationships between insufficient sleep and both diabetes and high blood pressure were also modestly attenuated but not fully explained by obesity. Conclusions Assessment of sleep quantity and quality and additional efforts to encourage optimal sleep and sleep health should be considered in routine medical examinations. Ongoing research designed to test treatments for obesity, mental distress, or various chronic diseases should also consider assessing the impact of these treatments on sleep health.